Hematite Photoanodes: Synergetic Enhancement of Light Harvesting and Charge Management by Sandwiched with Fe2TiO5/Fe2O3/Pt Structures. (20th October 2017) - Wang, Lei; Nguyen, Nhat Truong; Huang, Xiaojuan; Schmuki, Patrik; Bi, Yingpu
Abstract: Efficient charge separation and transport as well as high light absorption are key factors that determine the efficiency of photoelectrochemical (PEC) water splitting devices. Here, a PEC device consisting of a hematite nanoporous film deposited on Pt nanopillars, followed by the decoration with an Fe2 TiO5 passivation layer, is designed and fabricated. This structure can largely improve the light absorption in the composite materials, and significantly enhance the water oxidation performance of hematite photoanodes. The Fe2 TiO5 thin shell and Pt underlayer significantly improve the interfacial charge transfer while minimizing the hole‐migration length in Fe2 O3 photoanodes, leading to a drastically increased photocurrent density. Specially, the Fe2 TiO5 /Fe2 O3 /Pt photoanode yields an excellent photoresponse for PEC water splitting reactions with 1.0 and 2.4 mA cm −2 obtained at 1.23 and 1.6 VRHE under AM 1.5G illumination in 1m KOH. The resulting photocurrents are 2.5 times enhanced compared to a pristine Fe2 O3 photoanode of the same geometry. These results demonstrate a synergistic charge transfer effect of Fe2 TiO5 and Pt layers on hematite for the improvement of PEC water oxidation. Abstract : Synergetic enhancement of light harvesting and charge separation . The formation of a Fe2 TiO5 thin shell and a Pt underlayer on hematite photoanodes largely improves light absorption in the composite material, and also significantly enhances the water oxidation performance. The Fe2 TiO5 thin shell and Pt underlayer significantly improve the interfacial and surface charge separation efficiencies with minimized influence on the hole‐migration property of Fe2 O3 photoanodes.